An investigation on the patterns and antecedents of charitable giving behaviour among Muslims in Malaysia / Salwa Amirah Awang - Salwa Amirah , Awang (2017)
Internationally, charitable giving is recognized as an important monetary resource and highly encouraged in Islam as it has its own economic role that offers sustainability and societal welfare. This study intends to explore the patterns and antecedents of voluntary charitable giving in the Muslim world especially in Malaysia through a quantitative method of survey research design. An instrument in the form of a set of questionnaire was developed using the extended theory of Theory of Planned Behaviour (TPB). 1034 sets of questionnaire were gathered from the samples of working Muslim population in Malaysia using the cluster sampling involving Perak, Selangor, Pahang and Johor which were selected by the highest number of Muslim workers throughout Malaysia. The data was analyzed using the descriptive analysis, factor analysis, Partial Least Square of Structural Equation Modeling and Logistic Regression. Findings of the study discovered that Muslims in Malaysia mostly preferred to donate to worship house and beggars but less likely to donate to nonprofit institutions and higher education institutions and tended to use the conventional method of giving compared to technological methods. The result of factor analysis showed that the instrument had high value of validity and all components explained the charitable giving behaviour by 74.12%. The result of PLS SEM indicated that attitude, perceived behavioural control and altruism significantly influenced the intention to give with religiosity and financial wellness 1 and 2 moderated the relationship between perceived behaviour control and giving intention. While the result of logistic regression revealed significant factors for giving to six different categories such as worship house, religious school, beggars, charity homes, nonprofit institutions and higher education institutions in which variables such as age, gender, marital status education, employment, home ownership, household income, medium of information as well as the latent variables in the model were found to besignificant predictors for certain kinds of giving while tax was proven to be significant for all kinds of giving. The significance of this study can be viewed in three aspects. Firstly, from the theoretical aspect, this study elaborated on the concept of charity in Islam incrementally and provided empirical evidence to the relevance of the extended theory of TPB. From the aspect of methodology, it produced a valid and reliable instrument of charitable giving behaviour and steps of conducting cluster sampling. Finally, in practical aspect, it prepared insights to charity marketers especially to focus on significant areas and to stimulate contributing factors in order to increase fundraising and to collaborate with influential institutions among the public. Thus, it is hoped that the findings of this study will be benefited by all authorities involved in charity to further encourage the giving behaviour for the improvement of society welfare.